Laboratory Evaluation of Aspergillus Galactomannan Lateral Flow Assays - Ubbink, Anja (University of the Witwatersrand, Johannesburg, 2023)
Invasive aspergillosis diagnosis is based on a combination of clinical, radiological, and mycological factors, including the detection of Aspergillus galactomannan antigen in serum and bronchoalveolar lavage fluid (BALF). Lateral flow assays (LFA) introduced for rapid detection of galactomannan in serum and BALF include the IMMY sōna Aspergillus LFA (IMMY LFA) and the Dynamiker QuicGMTM Aspergillus Galactomannan Ag LFA (QuicGM LFA). Objective To evaluate the performance of the IMMY LFA and QuicGM LFA in South Africa. Methods Serum and BALF samples previously tested by Platelia BioRad Aspergillus GM-EIA were analysed using the two different LFAs. Percentage agreement and precision was assessed. Results Forty-six serum- and 13 BALF samples were tested using the IMMY GM LFA and 48 serum- and 6 BALF samples were tested using the QuicGM LFA. Using an optical density ≥0.5 as positive, results were compared to the BioRad Aspergillus GM-EIA. For the IMMY LFA, serum samples had a positive percent agreement (PPA) of 0% (0/1); negative percent agreement (NPA) of 91% (41/45) and overall percent agreement (OPA) of 89% (41/46). BALF samples had a PPA of 75% (3/4), NPA 50% (5/10) and OPA of 57% (8/14). For the QuicGM LFA, serum samples had a PPA 0% (0/3), NPA of 96% (43/45) and OPA of 90% (43/48). BALF samples had a PPA of 100% (1/1), NPA of 100% (5/5) and OPA of 100% (6/6). For the IMMY LFA, between-day reproducibility for 72% (13/18) and 63% (5/8) for serum and BALF samples, respectively. Between-batch reproducibility was 89% (16/18) and 50% (4/8), respectively for serum and BALF samples. For the QuicGM LFA, between-day reproducibility was 75% (9/12) and 75% (3/4) for the serum and BALF samples, respectively. The between-batch reproducibility was 100% (8/8) for serum and 100% (3/3) for BALF. Conclusion A follow-up evaluation with a larger sample size utilizing clinical, radiological, and laboratory data is warranted to determine the assays’ clinical utility. What this study adds Invasive aspergillosis is a life-threatening disease, where a prompt diagnosis improves outcome. Currently there is no Aspergillus galactomannan assay available in the South African state sector. This study evaluates two lateral flow assays for the detection of Galactomannan in South Africa
A research report submitted to the Faculty of Health Sciences in partial fulfillment of the requirements for the degree of Master of Medicine in Medical Microbiology, School of University of the Witwatersrand, Johannesburg, , Johannesburg, 2023
Keywords: Invasive Aspergillosis; Galactomannan; Lateral flow assay; UCTD; SDG-3: Good health and well-being